Perceived injury risk among elite track & field athletes — a questionnaire-based study - Mereman, M. (British Journal of Sports Medicine, 2021)
Background Studies of Swedish track and field athletes have shown that there is a substantial risk of injury. None of these studies have investigated the potential role of how athletes perceive their injury risk, and how it may play a part in the occurrence of sport injuries.